THE EXPLORATION OF VOCABULARY TEACHING STRATEGIES USED BY ENGLISH TEACHERS - Nur Syafa Malik; Haryanto Atmowardoyo; Maemuna Muhayyang (JTechLP: Journal of Technology in Language Pedagogy, 2026)
The objectives of this study are to identify the vocabulary teaching strategies used by English teachers at SMP Negeri 1 Wasuponda. This study is a qualitative descriptive research design with data collection techniques in the form of classroom observations. The participants of this study were three English teachers at SMP Negeri 1 Wasuponda. The results of the observations showed that teachers applied various vocabulary teaching strategies categorized into four groups: de-contextualizing strategies (word lists, flashcards, and dictionary use), semi-contextualizing strategies (word grouping, association, visual imagery, aural imagery, keyword, physical response, physical sensation, and semantic mapping), fully-contextualizing strategies (reading, listening, speaking, and writing), and adaptable strategies (structured reviewing). However, the findings also indicate that not all teachers implemented all of these strategies. Some strategies were applied only by certain teachers depending on their teaching preferences, classroom situations, and students’ learning needs. Based on the results of the study, it can be concluded that English teachers at SMP Negeri 1 Wasuponda employ a variety of vocabulary teaching strategies to support students’ vocabulary development, although the implementation of these strategies varies among teachers.